A porous TiO2 nanosheet modified polyethersulfone ultrafiltration membrane and preparation method thereof
By using porous TiO2 nanosheets as hydrophilic modifiers in polyethersulfone ultrafiltration membranes, the problem of easy contamination and limited nanoTiO2 modification effect in polyethersulfone ultrafiltration membranes is solved, and a significant improvement in high-purity water flux and small-molecular pollutant interception rate is achieved.
Patent Information
- Application Number
- CN202211386631.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-11-07
AI Technical Summary
The existing polyethersulfone ultrafiltration membranes are easily contaminated in applications, resulting in a decrease in water production, and nano-TiO2 modification methods have limited effectiveness in improving pure water flux and retention.
By adding a specific amount of polyethylene glycol, polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and tetra-acid zinc oxide whiskers in the preparation process of nano-TiO2, and performing gradient heat treatment, porous TiO2 nanosheets are obtained as hydrophilic modifiers for polyether sulfone ultrafiltration membrane.
The pure water flux and the retention rate of small-molecular pollutants of the modified polyethersulfone ultrafiltration membrane are significantly improved, and the hydrophilicity and anti-pollution ability of the membrane are enhanced.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of membrane preparation and relates to a porous TiO2 nanosheet modified polyethersulfone ultrafiltration membrane and a preparation method thereof. Background Art
[0002] Membrane separation technology is a new technology since the 21st century. It is widely used in the fields of separation, purification and concentration. It has the characteristics of simple and convenient operation process, mild operating conditions, no chemical reaction in the separation process, and good separation effect. The membrane separation processes that have been industrialized include reverse osmosis, nanofiltration, ultrafiltration and microfiltration. Among them, the average pore size of ultrafiltration is between 3 and 100nm. The process has the advantages of low operating pressure and is the most widely used.
[0003] Polyethersulfone has the advantages of high mechanical strength, high temperature resistance, wide pH range, good chlorine resistance, etc., and is often used as a raw material to prepare ultrafiltration membranes. However, polyethersulfone has strong hydrophobicity. In practical applications, pollutants are easily adsorbed to the membrane surface, forming filter cakes or blocking membrane pores, which greatly reduces the water production, thus affecting production. Membrane pollution has become a bottleneck restricting the further application and promotion of polyethersulfone ultrafiltration membranes. Therefore, it is necessary to perform hydrophilic modification on polyethersulfone ultrafiltration membranes to improve their anti-pollution and separation performance.
[0004] Nano-TiO2 has abundant hydrophilic functional groups on its surface, which is commonly used to hydrophilically modify the membrane. For example, CN107551828A discloses a method for preparing a PES-TiO2 nanowire blended ultrafiltration membrane, which includes adding a desired amount of TiO2 nanowires to a polyethersulfone casting solution, and then converting the membrane into a membrane by a solvent phase non-solvent phase method. CN106914154A discloses a method for preparing a PEG-TiO2 / PES / PVA ultrafiltration membrane, which includes hydrophilically modifying a PES / PVA composite ultrafiltration membrane using PEG-TiO2 as an additive. However, although the above method can improve the pure water flux and small molecule pollutant retention rate of the membrane to a certain extent, the improvement is still relatively limited. Summary of the invention
[0005] The present invention aims to provide a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane having both good pure water flux and small molecule pollutant interception rate and a preparation method thereof.
[0006] The prior art uses nano-TiO2 to modify the ultrafiltration membrane, and the reason why the pure water flux and the retention rate of the membrane are limited is that the addition of nano-materials will inevitably cause agglomeration on the membrane. Once agglomeration occurs, the membrane pores will be blocked, and the membrane permeability will be greatly reduced. After in-depth and extensive research, the inventors of the present invention found that in the preparation process of nano-TiO2, a specific amount of polyethylene glycol, polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and four needle-shaped zinc oxide whiskers are used as modifiers and preheating reaction and hydrothermal reaction are carried out at 50-60°C and 90-110°C in sequence, and the porous TiO2 nanosheets obtained thereby are used as the hydrophilic modification agent of the polyethersulfone ultrafiltration membrane, which can significantly improve the pure water flux and the retention rate of the modified polyethersulfone ultrafiltration membrane. The reason may be that: on the one hand, the synergistic effect of polyethylene glycol, polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and four-needle zinc oxide whiskers and gradient heat treatment can make the final nano-TiO2 porous TiO2 nanosheets. Compared with one-dimensional TiO2 nanoparticles, two-dimensional porous TiO2 nanosheets have larger microscopic sizes, weaker interaction between nanosheets, and are easier to disperse on the ultrafiltration membrane, which can effectively prevent agglomeration. In addition, the abundant hydrophilic groups such as hydroxyl and carboxyl groups on the porous TiO2 nanosheets greatly increase the hydrophilicity of the membrane, making it The anti-pollution ability is enhanced, and the porous structure on the porous TiO2 nanosheet provides an efficient nanochannel for water molecule transport, greatly increasing the membrane flux without reducing the interception, and the porous structure also achieves the interception of small molecule pollutants, which is not available in other ultrafiltration membranes; on the other hand, the four-needle zinc oxide whisker has a three-dimensional space structure, which is used as an additive in the preparation process of nano-TiO2, and can play a role in spacing and bridging the porous TiO2 nanosheet, so that the porous TiO2 nanosheet can be distributed in a three-dimensional space, which is more conducive to the improvement of its dispersibility. Based on this, the present invention is completed.
[0007] Specifically, the present invention provides a method for preparing a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane, wherein the method comprises:
[0008] S1. Tetrabutyl titanate, polyethylene glycol, polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and tetrapod-shaped zinc oxide whiskers are dispersed in a first solvent in a ratio of 1 mL: (5-10) mg: (40-60) mg: (100-200) mg, the obtained dispersion is preheated at 50-60° C. for 5-10 h, and then hydrothermally reacted at 90-110° C. for 10-30 h, the obtained hydrothermal reaction product is solid-liquid separated, and the obtained solid product is washed and dried to obtain porous TiO2 nanosheets;
[0009] S2, adding the porous TiO2 nanosheets to the second solvent and uniformly dispersing them by ultrasonication, then adding polyethersulfone and lithium chloride, magnetically stirring them at room temperature, and then degassing them under vacuum to obtain a casting solution;
[0010] S3. The non-woven fabric is attached to a glass plate, and then the casting liquid is poured onto the surface of the non-woven fabric and the film is scraped with a film scraper. After scraping, the obtained membrane is immediately placed in deionized water for phase conversion to obtain a polyethersulfone ultrafiltration membrane.
[0011] In the present invention, the ratio of tetrabutyl titanate, polyethylene glycol, polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and tetranepal-shaped zinc oxide whisker is 1 mL: (5-10) mg: (40-60) mg: (100-200) mg. Specifically, based on 1 mL of tetrabutyl titanate, the amount of polyethylene glycol is 5 to 10 mg, such as 5 mg, 6 mg, 7 mg, 8 mg, 9 mg, 10 mg, etc.; the amount of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer is 40 to 60 mg, such as 40 mg, 42 mg, 45 mg, 48 mg, 50 mg, 52 mg, 55 mg, 58 mg, 60 mg, etc.; the amount of four-needle zinc oxide whisker is 100 to 200 mg, such as 100 mg, 110 mg, 120 mg, 130 mg, 140 mg, 150 mg, 160 mg, 170 mg, 180 mg, 190 mg, 200 mg and any value therebetween.
[0012] In a preferred embodiment, in step S1, the polyethylene glycol is selected from at least one of PEG1000, PEG1500, PEG2000, PEG2500, PEG3350, PEG4000, PEG6000 and PEG8000.
[0013] In a preferred embodiment, in step S1, the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer is 1000-20000, such as 1000, 3000, 5000, 8000, 10000, 12000, 15000, 18000, 20000 and any value therebetween.
[0014] In a preferred embodiment, in step S1, the content of zinc oxide in the four-needle zinc oxide whisker is 99.9% to 100%, the length of the needle is 3 to 200 μm, and the diameter of the root of the needle is 0.1 to 10 μm.
[0015] In a preferred embodiment, in step S1, the first solvent is a mixture of deionized water and ethanol in a volume ratio of 10:(2-5); the volume ratio of tetrabutyl titanate to the first solvent is 1:(50-100).
[0016] In a preferred embodiment, in step S2, based on the total weight of the porous TiO2 nanosheets, the second solvent, polyethersulfone and lithium chloride as 100%, the amount of the porous TiO2 nanosheets is 0.5-2wt%, the amount of the second solvent is 65-75wt%, the amount of the polyethersulfone is 10-25wt%, and the amount of the lithium chloride is 5-15wt%.
[0017] In a preferred embodiment, in step S2, the second solvent is N-methylpyrrolidone.
[0018] In a preferred embodiment, in step S2, the magnetic stirring time is 20 to 30 hours; the degassing time is 1 to 10 hours.
[0019] In a preferred embodiment, in step S3, the scraping film has a thickness of 0.1 to 0.3 mm and a speed of 10 to 30 cm / s.
[0020] In a preferred embodiment, in step S3, the membrane is placed in deionized water for phase inversion by soaking the membrane in deionized water for more than 24 hours, and changing the water every 2 hours.
[0021] The invention also provides a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane prepared by the method.
[0022] The porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane provided by the present invention has both good pure water flux and interception rate for small molecule pollutants, and has great industrial application prospects. DETAILED DESCRIPTION
[0023] The present invention will be described in detail below by way of examples. The examples of the embodiments are intended to explain the present invention and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0024] Example 1
[0025] S1. Take 20 mL of deionized water and 50 mL of ethanol and add them to a conical flask, then add 2 mL of tetrabutyl titanate, 15 mg of PEG1000, 100 mg of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer (F127, purchased from Sigma-Aldrich, the same below) and 300 mg of four-needle zinc oxide whiskers (the content of zinc oxide is 99.9% to 100%, the length of the needle is 3 to 200 μm, and the diameter of the root of the needle is 0.1 to 10 μm, the same below), and transfer them to a hydrothermal reactor after ultrasonic dispersion for 30 minutes. Preheat the reaction at 55°C for 8 hours, and then hydrothermally react at 100°C for 20 hours. The obtained white product is washed three times with deionized water and ethanol respectively, and then dried to obtain porous TiO2 nanosheets;
[0026] S2, adding 0.5wt% of porous TiO2 nanosheets to 69.5wt% of N-methylpyrrolidone, followed by ultrasonic dispersion for 2h, then adding 20wt% of polyethersulfone and 10wt% of additive LiCl, magnetically stirring at room temperature for 24h to obtain a uniform casting solution, and degassing under vacuum for 5h for later use;
[0027] S3. Stick the non-woven fabric on the glass plate, pour the vacuum degassed casting liquid on the surface of the non-woven fabric, and use a scraper to scrape the film. Set the scraping thickness to 0.2mm and the scraping speed to 20cm / s. After scraping, immediately put the obtained membrane into deionized water for phase inversion. The membrane needs to be soaked in deionized water for more than 24h, and the water is changed every 2h to allow the solvent and non-solvent to be fully exchanged, and finally a porous TiO2 nanosheet modified polyethersulfone ultrafiltration membrane is obtained.
[0028] Example 2
[0029] S1. Take 20 mL of deionized water and 50 mL of ethanol and add them into a conical flask, then add 2 mL of tetrabutyl titanate, 10 mg of PEG1000, 120 mg of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer (F127, purchased from Sigma-Aldrich, the same below) and 200 mg of four-needle zinc oxide whiskers, transfer to a hydrothermal reactor after ultrasonic dispersion for 30 min, preheat the reaction at 50 ° C for 10 h, and then hydrothermally react at 110 ° C for 10 h. The obtained white product is washed three times with deionized water and ethanol respectively and then dried to obtain porous TiO2 nanosheets;
[0030] S2, adding 1wt% of porous TiO2 nanosheets to 69wt% of N-methylpyrrolidone, followed by ultrasonic dispersion for 2h, adding 20wt% of polyethersulfone and 10wt% of additive LiCl, and magnetically stirring at room temperature for 24h to obtain a uniform casting solution, and degassing under vacuum for 5h for use;
[0031] S3. Stick the non-woven fabric on the glass plate, pour the vacuum degassed casting liquid on the surface of the non-woven fabric, and use a scraper to scrape the film. Set the scraping thickness to 0.2mm and the scraping speed to 20cm / s. After scraping, immediately put the obtained membrane into deionized water for phase inversion. The membrane needs to be soaked in deionized water for more than 24h, and the water is changed every 2h to allow the solvent and non-solvent to be fully exchanged, and finally a porous TiO2 nanosheet modified polyethersulfone ultrafiltration membrane is obtained.
[0032] Example 3
[0033] S1. Take 20 mL of deionized water and 50 mL of ethanol and add them into a conical flask, then add 2 mL of tetrabutyl titanate, 20 mg of PEG1000, 80 mg of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer (F127, purchased from Sigma-Aldrich, the same below) and 400 mg of four-needle zinc oxide whiskers, transfer to a hydrothermal reactor after ultrasonic dispersion for 30 min, preheat the reaction at 60 ° C for 5 h, and then hydrothermally react at 90 ° C for 30 h. The obtained white product is washed three times with deionized water and ethanol respectively and then dried to obtain porous TiO2 nanosheets;
[0034] S2, adding 1.5wt% of porous TiO2 nanosheets to 68.5wt% of N-methylpyrrolidone, followed by ultrasonic dispersion for 2h, then adding 20wt% of polyethersulfone and 10wt% of additive LiCl, magnetically stirring at room temperature for 24h to obtain a uniform casting solution, and degassing under vacuum for 5h for use;
[0035] S3. Stick the non-woven fabric on the glass plate, pour the vacuum degassed casting liquid on the surface of the non-woven fabric, and use a scraper to scrape the film. Set the scraping thickness to 0.2mm and the scraping speed to 20cm / s. After scraping, immediately put the obtained membrane into deionized water for phase inversion. The membrane needs to be soaked in deionized water for more than 24h, and the water is changed every 2h to allow the solvent and non-solvent to be fully exchanged, and finally a porous TiO2 nanosheet modified polyethersulfone ultrafiltration membrane is obtained.
[0036] Example 4
[0037] A porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane was prepared according to the method of Example 1, except that in step S2, the amount of porous TiO2 nanosheets was 2wt% and the amount of N-methylpyrrolidone was 68wt%, and the other conditions were the same as in Example 1, to obtain a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane.
[0038] Comparative Example 1
[0039] A porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane was prepared according to the method of Example 4, except that the porous TiO2 nanosheets obtained in step S1 were replaced by the same weight portion of commercial TiO2 nanoparticles P25. The remaining conditions were the same as those of Example 4, and a reference porous TiO2 modified polyethersulfone ultrafiltration membrane was obtained.
[0040] Comparative Example 2
[0041] A porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane was prepared according to the method of Example 4, except that the porous TiO2 nanosheet obtained in step S1 was replaced by the same weight of TiO2 nanowires, and the other conditions were the same as those of Example 4 to obtain a reference porous TiO2-modified polyethersulfone ultrafiltration membrane. The TiO2 nanowires were prepared according to the following method:
[0042] 10 g of TiO2 powder was added to 300 mL of 10 mol / L sodium hydroxide solution, and the mixture was stirred for 20 min to obtain a mixed solution A; the mixed solution A was placed in a 100 mL polytetrafluoroethylene liner, placed in a reactor, and placed in an oven at a high temperature of 180°C for 48 h; the precipitate obtained after the reaction was washed with 0.1 M hydrochloric acid and deionized water, centrifuged and dried to obtain TiO2 nanowires.
[0043] Comparative Example 3
[0044] A porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane was prepared according to the method of Example 4, except that in step S1, PEG1000 was replaced by the same weight portion of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer F127, and the remaining conditions were the same as in Example 4 to obtain a reference porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane.
[0045] Comparative Example 4
[0046] A porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane was prepared according to the method of Example 4, except that in step S1, the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer F127 was replaced by the same weight portion of PEG1000, and the other conditions were the same as in Example 4 to obtain a reference porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane.
[0047] Comparative Example 5
[0048] A porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane was prepared according to the method of Example 4, except that in step S1, the four-needle zinc oxide whiskers were replaced by the same weight portion of polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer F127, and the other conditions were the same as in Example 4 to obtain a reference porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane.
[0049] Comparative Example 6
[0050] A porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane was prepared according to the method of Example 4, except that in step S1, after ultrasonic dispersion and transfer to a hydrothermal reactor, the hydrothermal reaction was directly carried out at 100°C for 28 hours (i.e., no preheating reaction treatment was performed), and the remaining conditions were the same as in Example 4 to obtain a reference porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane.
[0051] Test Case
[0052] (1) Water contact angle: measured by JC2000C1 contact angle meter. The results are shown in Table 1.
[0053] (2) Pure water flux: The pure water flux of a membrane is an important parameter that indicates the hydrophilicity of the membrane. It means: the volume of water filtered by a membrane of a certain size under a stable operating pressure for a certain period of time, and the unit is L / (m 2 ·h). The commonly used calculation formula is as follows: Jw=Vw / (A×T), where: Jw represents the pure water flux L / (m 2 h), Vw represents the volume of pure water passing through L, A represents the effective membrane area m 2 , T represents the time h required for pure water to pass through Vw. The pure water flux was tested at 0.1 MPa. The results are shown in Table 1.
[0054] (3) Retention rate of bovine serum albumin (BSA) and polyethylene glycol (PEG): The retention performance of the membrane for 67000Da bovine serum albumin and 2000Da polyethylene glycol was calculated according to the following formula: R = (Cconcentrated - Cdiluted) / Cdiluted, where: R represents the retention rate, Cconcentrated represents the concentration of the solution before ultrafiltration, and Cdiluted represents the concentration of the solution after ultrafiltration. The retention rate was tested at 0.1MPa. The results are shown in Table 1.
[0055] Table 1
[0056] serial number Water contact angle <![CDATA[Pure water flux L / (m 2 ·h)]]> BSA Retention % PEG retention % Example 1 52.1° 489.2 95.1 10.1 Example 2 47.2° 482.6 95.8 11.2 Example 3 41.6° 490.1 94.2 12.3 Example 4 36.7° 483.2 95.6 11.5 Comparative Example 1 69.5° 280.7 92.7 0 Comparative Example 2 76.1° 250.2 87.5 0 Comparative Example 3 68.3° 285.6 92.9 1.2 Comparative Example 4 68.8° 823.5 92.8 1.2 Comparative Example 5 72.9° 266.8 89.1 0.8 Comparative Example 6 67.6° 288.3 93.0 1.5
[0057] The water contact angle can be understood as a special angle formed between the liquid and the solid when the liquid is dropped on a solid surface. The water contact angle is divided by 90°. When it is greater than this angle, it is non-wetting, and when it is less than this angle, it is wettable. Therefore, the size of the water contact angle is usually measured to measure the hydrophilicity of the membrane. That is, when the water contact angle of the membrane is small, the surface wettability of the membrane is good, otherwise the membrane is hydrophobic. The hydrophilicity and hydrophobicity of the membrane can reflect the anti-pollution ability of the membrane to a certain extent. When the membrane is hydrophilic, water molecules are more likely to form a hydration layer between the membrane material, thereby preventing hydrophobic pollutants from contacting the membrane surface and slowing down membrane pollution.
[0058] As shown in Table 1 above, the hydrophilicity of the porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane provided by the present invention is significantly better than that of the polyethersulfone ultrafiltration membrane obtained in the comparative example, indicating that it has better anti-pollution ability. The water contact angle of the ultrafiltration membrane in the comparative example is as high as 76.1°, which may be because the added TiO2 nanoparticles will agglomerate on the membrane and fail to effectively improve the hydrophilicity of the membrane.
[0059] As shown in Table 1 above, the flux of the porous TiO2 nanosheet modified polyethersulfone ultrafiltration membrane is significantly higher than that of the comparative example. This may be because the addition of the porous TiO2 nanosheet greatly improves the hydrophilicity of the membrane, and its porous structure provides a special transport channel for the transport of water molecules. The porous TiO2 nanosheet modified polyethersulfone ultrafiltration membrane provided by the present invention not only has a high flux, but also can reach a retention rate of more than 94.2% for BSA, which is higher than that of the comparative example. This may be because its good hydrophilicity makes it difficult for BSA to pass through the membrane. In terms of interception of low molecular weight polyethylene glycol, the comparative example ultrafiltration membrane is basically unable to intercept, while the ultrafiltration membrane in the embodiment can reach a retention rate of more than 10% for low molecular weight polyethylene glycol. This may be because the porous structure in the added porous TiO2 nanosheet is mesoporous, which can intercept low molecular weight polyethylene glycol.
[0060] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A method for preparing a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane, characterized in that: The method includes: S1. Tetrabutyl titanate, polyethylene glycol, polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer and tetrapod-shaped zinc oxide whiskers are dispersed in a first solvent in a ratio of 1 mL: (5-10) mg: (40-60) mg: (100-200) mg, the obtained dispersion is preheated at 50-60° C. for 5-10 h, and then hydrothermally reacted at 90-110° C. for 10-30 h, the obtained hydrothermal reaction product is solid-liquid separated, and the obtained solid product is washed and dried to obtain porous TiO2 nanosheets; S2, adding the porous TiO2 nanosheets to the second solvent and uniformly dispersing them by ultrasonication, then adding polyethersulfone and lithium chloride, magnetically stirring them at room temperature, and then degassing them under vacuum to obtain a casting solution; S3. The non-woven fabric is attached to a glass plate, and then the casting liquid is poured onto the surface of the non-woven fabric and the film is scraped with a film scraper. After scraping, the obtained membrane is immediately placed in deionized water for phase conversion to obtain a polyethersulfone ultrafiltration membrane.
2. The method for preparing a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane according to claim 1, characterized in that: In step S1, the polyethylene glycol is selected from at least one of PEG1000, PEG1500, PEG2000, PEG2500, PEG3350, PEG4000, PEG6000 and PEG8000.
3. The method for preparing a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane according to claim 1, characterized in that: In step S1, the number average molecular weight of the polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer is 1,000 to 20,000.
4. The method for preparing a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane according to claim 1, characterized in that: In step S1, the content of zinc oxide in the four-needle zinc oxide whisker is 99.9% to 100%, the length of the needle is 3 to 200 μm, and the diameter of the root of the needle is 0.1 to 10 μm.
5. The method for preparing a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane according to claim 1, characterized in that: In step S1, the first solvent is a mixture of deionized water and ethanol in a volume ratio of 10:(2-5); the volume ratio of tetrabutyl titanate to the first solvent is 1:(50-100).
6. The method for preparing a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane according to claim 1, characterized in that: In step S2, based on the total weight of the porous TiO2 nanosheets, the second solvent, polyethersulfone and lithium chloride as 100%, the amount of the porous TiO2 nanosheets is 0.5-2wt%, the amount of the second solvent is 65-75wt%, the amount of the polyethersulfone is 10-25wt%, and the amount of the lithium chloride is 5-15wt%; the second solvent is N-methylpyrrolidone.
7. The method for preparing a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane according to claim 1, characterized in that: In step S2, the magnetic stirring time is 20 to 30 hours; the degassing time is 1 to 10 hours.
8. The method for preparing a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane according to claim 1, characterized in that: In step S3, the thickness of the scraping film is 0.1-0.3 mm and the speed is 10-30 cm / s.
9. The method for preparing a porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane according to claim 1, characterized in that: In step S3, the membrane is placed in deionized water for phase inversion by soaking the membrane in deionized water for more than 24 hours, and changing the water every 2 hours.
10. A porous TiO2 nanosheet-modified polyethersulfone ultrafiltration membrane prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method and applications of PEG-TiO2 / PES / PVA hydrophilic ultra-filtration membrane
CN106914154A
PES-TiO2 nanowire blend ultrafiltration membrane and preparation method and application thereof
CN107551828A
Hollow fiber ultrafilter membrane with poly(phthalazinone ether fulfone), poly(phthalazinone ether ketone) or poly(phthalazinone ether sulfone ketone) and preparation thereof
WO2004096418A1